Effectiveness of Pelvic Organ Prolapse Surgery in Women with Depressive Symptoms and Decreased Quality of Life - Susanto, Azhar; Fauzi, Amir; Rusydi, Syakroni D; Theodorus, Theodorus; Sahab, Abdullah (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To know the effectiveness of pelvic organ prolapse surgery in decreasing depressive symptoms (based on PHQ9) and improving quality of life in women with pelvic organ prolapse. Methods: This experimental study without control is conducted at the Obstetrics and Gynecology Department of Dr. Mohammad Hoesin Hospital Palembang/Faculty of Medicine Sriwijaya University, from October 03 2012 until May 31, 2014. Data containing selfadministrated questionnaire about depressive symptoms (PHQ9) and quality of life (PFIQ and PFDI) were recorded. Questionnaire was performed before and six months after surgery. Sample included 26 women with pelvic organ prolapse seeking pelvic organ prolapse surgery, which qualified the inclusion criteria. Data were analyzed using Chi Square and Fisher Exact test. Data analysis was done using SPSS 18.0. Results: According to paired T test there is a significant difference between mean PHQ9 score before (6.69±3.80) and 6 months after surgery (1.96±1.75)(p=0.001). Total PFIQ score decreased from 17.15±9.39 to 2.88±4.01 with 14.27±5.38 reduction. PFDI score before surgery were 29.85±15.73 and decreased to 11.50±10.99, with a reduction of 18.35±4.74. Conclusion: There was significant reduction in depressive symptoms and improved quality of life in women with prolapse after surgery, compared to before surgery. [Indones J Obstet Gynecol 2015; 3-4: 196-199] Keywords: depression, quality of life, uterine prolapse